Sensitivity and Specificity of the ECAS in Parkinson’s Disease and Progressive Supranuclear Palsy - Jennifer A. Foley; Elaine H. Niven; Andrew Paget; Kailash P. Bhatia; Simon F. Farmer; Paul R. Jarman; Patricia Limousin; Thomas T. Warner; Huw R. Morris; Thomas H. Bak; Sharon Abrahams; Lisa Cipolotti (Parkinson's Disease)
Disentangling Parkinson’s disease (PD) and progressive supranuclear palsy (PSP) may be a diagnostic challenge. Cognitive signs may be useful, but existing screens are often insufficiently sensitive or unsuitable for assessing people with motor disorders. We investigated whether the newly developed ECAS, designed to be used with people with even severe motor disability, was sensitive to the cognitive impairment seen in PD and PSP and able to distinguish between these two disorders. Thirty patients with PD, 11 patients with PSP, and 40 healthy controls were assessed using the ECAS, as well as an extensive neuropsychological assessment. The ECAS detected cognitive impairment in 30% of the PD patients, all of whom fulfilled the diagnostic criteria for mild cognitive impairment. The ECAS was also able to detect cognitive impairment in PSP patients, with 81.8% of patients performing in the impaired range. The ECAS total score distinguished between the patients with PSP and healthy controls with high sensitivity (91.0) and specificity (86.8). Importantly, the ECAS was also able to distinguish between the two syndromes, with the measures of verbal fluency offering high sensitivity (82.0) and specificity (80.0). In sum, the ECAS is a quick, simple, and inexpensive test that can be used to support the differential diagnosis of PSP.